Digital Marketing for Halal Tourism Provider: A Review - Noradilah Abdul Hadi; Nur Shuhada Kamarudin; Nurul Nazlia Jamil; Nurshamimitul Ezza Ramli; Mohd Rizal Muwazir (Universiti Sains Islam Malaysia, 2024)
Halal market becomes one of the most profitable market at present and has shown promising growth particularly in Malaysia. The concept of halal is not only limited to food consumption, but also covers halal tourism which consists of halal hotels, halal transport (airlines), halal restaurants, halal tour packages and halal finance. Majority of tourists got information through travel websites, social media, blogs, travel agencies and advertising. This signifies the importance of digital marketing as the internet has changed the way people communicating and interacting with each other. This study aims to explore the concept of digital marketing and its potential in enhancing marketing strategies for halal tourism provider based on critical review of literature. Halal tourism providers have been encouraged to improve their tourism promotion signifying the importance of digital promotion to increase global outreach of halal tourism services.